Multidimensional analysis suggests that ZNF433 is a promising biomarker for the diagnosis and prognosis of human cancers - Xie, Lingyu; Zeng, Xin; Luo, Hui; Xie, Bin; Wang, Xuefeng; Wu, Nan; Zou, Junrong; Zhang, Guoxi; Zou, Xiaofeng; Xu, Hui (Frontiers in Oncology, 2025)
BackgroundZinc finger proteins, particularly members of the Krüppel-associated box zinc finger proteins (KRAB-ZFPs), play critical roles in regulating gene expression, cell cycle progression, and epigenetic modifications. Despite the growing body of research on KRAB-ZFPs, the role of ZNF433, a relatively less studied member of this family, remains poorly understood in the context of cancer.MethodsWe conducted multi-dimensional analyses using publicly available databases, including TCGA and GTEx, to evaluate ZNF433’s expression patterns, genetic mutations, survival outcomes, immune microenvironment interactions, and diagnostic potential across different cancers. Functional enrichment and protein interaction network analyses were also performed to explore its potential involvement in cancer-related pathways.ResultsOur findings revealed that ZNF433 is significantly downregulated in most cancer types, with stage-dependent expression patterns observed in KIRC and KIRP. High expression of ZNF433 was associated with improved overall survival (OS) in HNSC and KIRC, while in ESCA and PRAD, it was correlated with poorer disease-free survival (DFS). Additionally, high ZNF433 levels were linked to better DFS in BRCA, KIRP, THYM, and KIRC. ZNF433 expression was also closely associated with genomic instability markers, including tumor mutational burden (TMB), microsatellite instability (MSI), and mismatch repair (MMR) deficiencies. Furthermore, ZNF433 exhibited significant regulatory roles within the tumor immune microenvironment. Diagnostic analysis showed that ZNF433 has strong diagnostic potential in LAML and TGCT, and moderate diagnostic value in other cancers.ConclusionsOur study highlights the potential of ZNF433 as a diagnostic and prognostic biomarker and provides new insights into its potential as a therapeutic target.